Wine Dilates the Brachial Artery but does not Increase Flow-mediated Dilatation over Two Hours - Blackhurst, D.M.; Wolmarans, K.H.; Marais, A.D (South African Journal of Enology and Viticulture, 2016)
Epidemiological evidence suggests cardiovascular benefits from the consumption of alcoholic beverages, but corroboration by functional and outcome studies is still outstanding. Non-invasive functional tests on the brachial arteries of healthy volunteers were performed before and for two hours after consuming red wine. Brachial artery dimensions were determined by ultrasound at baseline, 30, 60 and 120 min. Flow-mediated dilatation (FMD) was similarly assessed. Putative minimum and maximum lumen diameters were determined after ice immersion and sublingual trinitroglycerine (TNG) at baseline and 60 min after wine consumption. Sixteen subjects had a mean resting brachial artery diameter of 3.84 mm, which significantly increased with wine to 4.44 mm at 30 min, 4.39 mm at 60 min and 4.49 mm at 120 min. The calculated blood flow rates during the study did not differ significantly over the measured intervals. The baseline mean diameter with TNG was not significantly different from the dilation with wine. The vasoconstrictor response varied, with a -2.6 ± 2.9% change with wine, compared with the baseline diameter. There was appreciable variation of the diameter relative to the range found with ice and TNG. The calculated FMDs (% changes) for the study were 10.8, 6.1, 5.6 and 7.5, indicating statistically significant effects of wine (p < 0.0001). The authors conclude that red wine consumption leads to beneficial arterial effects that may relate to different doses or other mechanisms than FMD. Further studies need to be done to discriminate between the effects of alcohol and phenolic compounds on vascular function.